Efficacy of Calcium Phosphosilicate (CPS) Putty As Alloplastic Bioactive Graft Material in Sinus Augmentation Procedures: An Original Study - S.Girish, Rao; Sushma, Mehta; Abhishek, Singh Nayyar (Journal of Dentistry And Oral Implants, 2016)
Background and Context: Autologous bone grafts require a second surgical exposure to harvest the graft with a significant risk of post-operative complications and donor site morbidity. Employment of allografts potentially eliminates donor site morbidity but carries the potential of causing foreign body immune reactions with a high rate of rejection and failures. Hence, Alloplasts have emerged as novel materials to overcome the drawbacks of autogenous and allogenous bone grafts. Today’s advanced dentistry is enterprising a putty form of calcium phosphosilicate (CPS) into several aspects of reconstructive domain of dentistry including the sinus augmentation procedures, osseous regeneration of periodontal bone defects, cystic cavity defects and alveolar socket preservation. This eccentric multifaceted study was planned as an honest effort on the path of proving the efficiency of CPS as an alloplastic bioactive graft material and aimed at quantitative evaluation of regenerated bone radiographically using Cone Beam Computed Tomography (CBCT) scans following sinus augmentation procedures. Materials and Methods: A total of 20 sinus augmentations were carried-out in 17 patients satisfying the criteria (inclusion and exclusion) requiring placement of implants in atrophic maxilla and in other situations of anatomic constraints. The graft material used was calcium phosphosilicate (CPS) putty (Nova bone dental putty, Novabone products, Alachua, Fla). The residual bone height was recorded using CBCT scans and a computer based software where the measurements were made from the crest of the ridge till the sinus floor lining. The patients were assessed clinically at immediate post-operative, 1 week, 1 month, 3 months and 6 months follow-up recalls post-operatively. Radiographic assessment for bone height was done pre-operatively and at 6 months follow-up recall post-operatively using Cone Beam Computer Tomography scans. Results: The post-treatment bone height (11.76+0.97mm) was found to be significantly higher than the pre-treatment bone height (6.8 +0.70mm) in indirect sinus augmentation procedures (t=14.4, p<0.005). In case of direct sinus augmentation group also, the post-treatment bone height (11.27 +0.71mm) came-out to be significantly higher than the pre-treatment bone height (2.44 +0.81mm) (t=32.17, p<0.005). The post-treatment bone grafted sinus floor measurements (1107.6 + 155.6mm) were also found to be significantly higher than the original sinus floor measurements of bone density (Grayscale values) (412+ 65.5mm) (t=16.6, p<0.001) in case of indirect sinus augmentation procedures. Similarly, the post-treatment bone grafted sinus floor measurements (1169.6+136.7mm) were found to be significantly higher than the original sinus floor measurements of bone density (Grayscale values) (416.4+ 0.70mm) (t=17.9, p<0.001) in case of direct sinus augmentation group. Conclusion: Calcium Phosphosilicate (CPS) was accepted well at the recipient sites without any complications demonstrating its efficiency and reliability in sinus augmentation procedures.
Keywords: Indirect sinus augmentation; direct sinus augmentation; bone widh; bone height; bone density; Calcium Phosphosilicate (CPS)